The Victorian social-problem novel : the market, the individual, and communal life - Guy, Josephine M. (London: Macmillan Press, 1996)
The critical history of Victorian social-problem novels maps many of the changes in the theory and practice of literary history in the second half of the twentieth century. Josephine M. Guy's account of various critical responses to these enduringly popular works examines a range of approaches, particulary those of historicist, new-historicist and Marxist critics. Her own critical account of the sub-genre is built around close readings of such core texts as Hard Times, Mary Barton, North and South, Sybil, Alton Locke and Felix Holt. By focusing on the intellectual context in which these novels were produced - on the Victorians' debates about 'the social'and their understanding of what is meant by a 'social problem' - she recharacterises an important moment in mid-nineteenth-century literary history